FOUNDATIONS OF GEOPHYSICAL ELECTROMAGNETIC THEORY AND METHODS - Zhdanov, Michael S., author 356466 (Amsterdam, Netherlands ; Cambridge, MA, United States : Elsevier Science)
"Foundations of Geophysical Electromagnetic Theory and Methods, Second Edition, builds on the strength of the first edition to offer a systematic exposition of geophysical electromagnetic theory and methods. This new edition highlights progress made over the last decade, with a special focus on recent advances in marine and airborne electromagnetic methods. Also included are recent case histories on practical applications in tectonic studies, mineral exploration, environmental studies and off-shore hydrocarbon exploration. The book is ideal for geoscientists working in all areas of geophysics, including exploration geophysics and applied physics, as well as graduate students and researchers working in the field of electromagnetic theory and methods."--